Effect Of Kemangi (Ocimum basilicum) Extract in Spermatozoa Quality of Mice (Mus musculus) Exhibited to Cigarette Smoke - Sholihin, Ahnan; Ducha, Nur (LenteraBio : Berkala Ilmiah Biologi, 2024)
Smoking can cause infertility due to free radicals from cigarette smoke. Basil leaves contain antioxidants such as tannins and flavonoids to prevent free radicals. This study aims to determine the effect of basil leaf extract on the quality of spermatozoa exposed to cigarette smoke. This study was an experimental study with a completely randomized design (CRD), using 20 male mice aged 2-2.5 months were divided into five groups, namely K1 (positive control), K0 (negative control), P1 (100mg/kgBB extract dose), P2 (200mg/kgBB extract dose, P3 (300mg/kgBB extract dose). The mice exposed to cigarette smoke 2.5 cigarettes/day for 14 days, sperm quality calculated for motility, viability, membrane integrity, and abnormality. Data on spermatozoa analyzed by the One Way ANOVA test, and to determine the best treatment was performed by the Duncan test. The results showed that basil leaf extract affected the quality of spermatozoa (p>0.05). The best effect showed by a dose of 300mg/kgBB (P3) in improving the quality of mice spermatozoa. In conclusion, the dose of basil leaf extract is the most influential in increasing motility, viability, membrane integrity, and reducing abnormalities in mice spermatozoa.